Rethinking the Connection Between Creative Clusters and City Branding: the Cultural Axis of Piraeus Street in Athens - Karachalis, Nicholas; Deffner, Alex (Quaestiones Geographicae, 2012)
As culture and the arts gain importance within the agendas of cities, the operation of urban creative clusters is manifested as an effective planning tool for rundown neighbourhoods. Artists and cultural businesses (galleries, theatres, design offices, fashion designers, etc.) form a unique and distinctive sector among other sectors of the economy; their effect on the development and image of a particular neighbourhood can be very important. As part of wider urban processes, city marketing and city branding techniques are often used in order to promote the change in these neighbourhoods and, ideally, prevent negative social effects. The main goal of this paper is to present the experience and implications of the – mostly accidental – formation of a creative cluster in Athens (in the areas surrounding the Athenian part of Piraeus Street) and to critically evaluate the potential role of branding, drawing on the experience of similar efforts in other European cities.